Effect of Gallic Acid on Distant Organ Stomach in Intestinal Ischemia Reperfusion Injury - Başaran, Süreyya Özdemir; Kaplan, Özge; Aşır, Fırat (Journal of Drug Delivery and Therapeutics, 2023)
Aim: To examine the effects of gallic acid (GA) in the stomach in rats undergoing intestinal ischemia/reperfusion (IR) with Beclin -1 immunostaining.Material-Metod: 24 male Wistar albino rats were divided into control, IR and IR+GA groups. For the IR protocol, 60 minutes of ischemia and reperfusion were applied. The small intestines of the rats in the control group were removed by laparotomy and the abdomen was closed without applying anything else. Ischemia and reperfusion was applied to the superior mesenteric artery (SMA) for 60 minutes with a clamp in rats in the IR group. The blood flow was stopped with a clamp on the SMA of the rats in the IR+GA group and ischemia was applied for 60 minutes. 50 mg/kg gallic acid was given intraperitoneally to the animals, 60 minutes of reperfusion was performed, and the abdomen was closed. The stomach tissues were placed in paraffin blocks after routine histological follow-ups. Five micrometer-thick sections were taken from the paraffin blocks and stained with Hematoxylin-eosin and Beclin-1 immunostaining.Results: In the IR group, degeneration of gastric folds, apoptosis of epithelial cells and degeneration of lamina muscularis were observed. In the IR + GA group, gastric folds improved, but cell infiltration in the lamina propria and degeneration in the muscular layer were observed. Beclin-1 expression was positively observed in the surface epithelial cells and gastric glands in the control group. In the IR group, it was observed that the gastric folds were positive on the surface cells and negative in the submucosa, while in the IR + GA group, it was intensely expressed in the gastric epithelium and gastric glands.Conclusion: By increasing the expression of beclin-1, GA treatment induced autophagy in gastric mucosal cells, triggered the destruction of damaged cells and provided restoration of the mucosal layer.Keywords:   Beclin-1, gallic acid, apoptosis